Balneology research in Italy: facts and perspectives - Vaccarezza, Mauro; Vitale, Marco (Anales de Hidrología Médica, 2012)
Italy presently promotes relevant scientific research of modern thermalism and significant collaboration with health care Authorities. Even in a evidence-based discipline such as balneology, we can monitor the effects of the active ingredients contained in a particular type of water and, at the same time foster a modern clinical research approach that assesses the true action of balneology on patients. The Italian Granting Agency for Research in Balneotherapy (FoRST) periodically invites grant proposals in the Biomedical SPA basic and clinical research area. The selection process is based on the most acclaimed international criteria to evaluate scientific quality, appropriate money allocation, and overall feasibility of the project. Together with other European health institutions, FoRST is actively involved to improve the overall knowledge in crenotherapy also at the educational level and in collaboration with WHO is working to define skills and intervention fields of thermal medicine as well as an in depth quality review of worldwide scientific spa literature.